Maternal depression as a risk factor for children's inadequate housing conditions. (January 2016) - Corman, Hope; Curtis, Marah A.; Noonan, Kelly; Reichman, Nancy E.
Abstract: Depression among mothers with young children is an important public health issue that not only has implications for their own well-being, but can also potentially affect their children's health and developmental trajectories. This study explored the extent to which maternal depression is a risk factor for inadequate housing conditions related to utilities, a noteworthy risk factor for poor child health. Using data on 2965 mothers and children from a national urban cohort of U.S. births in 1998–2000, we estimated multivariate logistic regression models of associations between maternal depression during the postpartum year and a U.S. Department of Housing and Urban Development (HUD) measure of severely inadequate housing due to heating issues, as well as a broader measure of energy insecurity that encompasses various types of utility problems. We also considered outcomes that incorporated housing instability and food insecurity in conjunction with housing inadequacy. Mothers who experienced depression had about 60% higher odds of experiencing severely inadequate housing due to heat (OR: 1.57) and 70% higher odds of experiencing energy insecurity (OR: 1.69) compared to mothers who did not experience depression. Maternal depression was even more strongly associated with multiple hardships in the forms of housing inadequacy plus housing instability and/or food insecurity than it was with housing inadequacy. This study provides robust evidence that maternal depression is a risk factor for inadequate housing and multiple hardships during a critical period of children's development. The findings suggest that policy efforts should not occur in mental health, housing, and food security silos. Highlights: Maternal depression is a risk factor for severely inadequate housing. Maternal depression is a risk factor for household energy insecurity. Maternal depression is strongly associated with multiple hardships. Policy efforts should not occur in mental health, housing, and food silos.